Insecticide-treated plastic tarpaulins for control of malaria vectors in refugee camps - Graham, K.; Mohammad, N.; Rehman, H.; Nazari, A.; Ahmad, M.; Kamal, M.; Skovmand, O.; Guillet, P.; Allan, R.; Zaim, M.; Yates, A.; Lines, J.; et al. (Medical and veterinary entomology, 2002)
Spraying of canvas tents with residual pyrethroid insecticide is an established method of malaria vector control in tented refugee camps. In recent years, plastic sheeting (polythene tarpaulins) has replaced canvas as the utilitarian shelter material for displaced populations in complex emergencies. Advances in technology enable polythene sheeting to be impregnated with pyrethroid during manufacture. The efficacy of such material against mosquitoes when erected as shelters under typical refugee camp conditions is unknown. Tests were undertaken with free‐flying mosquitoes on entomological study platforms in an Afghan refugee camp to compare the insecticidal efficacy of plastic tarpaulin sprayed with deltamethrin on its inner surface (target dose 30 mg/m2), tarpaulin impregnated with deltamethrin (initially ≥ 30 mg/m2) during manufacture, and a tent made from the factory impregnated tarpaulin material. Preliminary tests done in the laboratory with Anopheles stephensi Liston (Diptera: Culicidae) showed that 1‐min exposure to factory‐impregnated tarpaulins would give 100% mortality even after outdoor weathering in a temperate climate for 12 weeks. Outdoor platform tests with the erected materials (baited with human subjects) produced mosquito mortality rates between 86–100% for sprayed or factory‐impregnated tarpaulins and tents (average ˜40 anophelines and ˜200 culicines/per platform/night), whereas control mortality (with untreated tarpaulin) was no more than 5%. Fewer than 20% of mosquitoes blood‐fed on human subjects under either insecticide‐treated or non‐treated shelters. The tarpaulin shelter was a poor barrier to host‐seeking mosquitoes and treatment with insecticide did not reduce the proportion blood‐feeding. Even so, the deployment of insecticide‐impregnated tarpaulins in refugee camps, if used by the majority of refugees, has the potential to control malaria by killing high proportions of mosquitoes and so reducing the average life expectancy of vectors (greatly reducing vectorial capacity), rather than by directly protecting refugees from mosquito bites. Mass coverage with deltamethrin‐sprayed or impregnated tarpaulins or tents has strong potential for preventing malaria in displaced populations affected by conflict.